MEANING OF LIFE IN BANYUWANGI TRADITIONAL DANCERS - Arni Nur Laila; Nandang Rusmana (OPTIMA: Journal Of Guidance and Counseling, 2021)
: Meaning of life is the value of life that needs to be realized to be interpreted by each individual in carrying out his life process. Traditional dancers are part of society and have their uniqueness. The study of the meaning of life in Banyuwangi traditional dance dancers was carried out with a qualitative approach to phenomenological studies through interviews and field observations as well as social media to students with dancer backgrounds. Their Findings meaning of life are three dancers, namely 1) dancing as a necessity; 2) dancing as selfexpression; and 3) dancing as an escape. The meaning of life possessed by dancers can become a frame of reference for providing services for counselors to students with dancer backgrounds